2006
DOI: 10.1007/s10535-006-0051-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic diversity in varieties of Mucuna pruriens using RAPD

Abstract: Genetic diversity was estimated in 13 accessions of the otherwise self pollinated Mucuna pruriens (L.) DC. (velvetbean) comprising varieties pruriens and utilis collected from tropical humid forest using 15 RAPD primers. Similarity index value of 0.68 based on Nei and Li's similarity coefficient indicated high degree of genetic variability. Analysis of various genetic diversity indices like total heterozygosity, Nei's gene diversity, percentage of polymorphic loci, expected and observed number of alleles and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 16 publications
4
20
0
1
Order By: Relevance
“…Therefore, the observed high levels of polymorphism detected in otherwise self-pollinated accessions of A. rugosa may be attributable to the broad genetic base of the species that in the process of speciation may have acquired novel gene combinations for better adaptability to changing environmental conditions. A similar observation of high diversity in a selfpollinated species has been reported in Mucuna pruriens (Capo-chichi et al, 2003;Padmesh et al, 2006). The high genetic diversity observed in A. rugosa may be due to its wide geographical and climatic distribution in both tropical and temperate regions that must have accelerated the evolvement of novel and diverse genotypes.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, the observed high levels of polymorphism detected in otherwise self-pollinated accessions of A. rugosa may be attributable to the broad genetic base of the species that in the process of speciation may have acquired novel gene combinations for better adaptability to changing environmental conditions. A similar observation of high diversity in a selfpollinated species has been reported in Mucuna pruriens (Capo-chichi et al, 2003;Padmesh et al, 2006). The high genetic diversity observed in A. rugosa may be due to its wide geographical and climatic distribution in both tropical and temperate regions that must have accelerated the evolvement of novel and diverse genotypes.…”
Section: Discussionsupporting
confidence: 74%
“…pruriens is by far the most investigated species for the study of intra species genetic and chemodiversity. Previously, many workers have studied and estimated the genetic diversity in both cultivated and wild Mucuna pruriens and its varieties using RAPD and morpho-agronomical characters, and found that M. pruriens has high genetic variation (Padmesh et al 2006;Kalidas and Mohan 2010;Sathyanarayana et al 2012). But very few studies have attempted to study the genetic diversity among the various Mucuna species.…”
Section: Discussionmentioning
confidence: 99%
“…Padmesh et al (2006) proved the potential use of RAPD to estimate intra-specific variation in Mucuna pruriens that could not be detected by sequence based ITS approach. Gielis et al (1997) demonstrated that the RAPD approach could generate reliable markers that are useful for establishing species relationships in Phyllostachys and bamboos in general.…”
Section: Introductionmentioning
confidence: 97%